PENDIDIKAN DAN PELATIHAN PEMBIBITAN JERUK BEBAS PENYAKIT CVPD (Citrus Vein Phloem Degeneration) DI DESA KATUNG KINTAMANI - W, Adiartayasa; Darmiati, N.N.; Simpati, I K. (Buletin Udayana Mengabdi, 2012)
The community service in the form of training about free orange seed of disease CVPD (Citrus Vein Phloem Degenaration) was conducted in Katung village, district of Kintamani, Bangli regency on 10 August 2007. The training activity aimed to improve knowledge of farmers about CVPD disease, symptom, transmission, insect vector, and integrated pest management. The topics covered were disease symptoms, and pathogen bacteria, Diaphorina citri are as insect vector infection mechanism, election of free orange mains crops CVPD, disease distribution and integrated management of CVPD. The training was attended by 25 participants from local groups of Katung village. The methods used in this activity were lectures, demonstration and practical work in the citrus field. All participants enthusiastically took part and hoped to have the next intensive training of citrus culture.